Extent of Availability of Prerequisites for The Applicationof ‎Lean Accounting in Industrial Companies - Khalf , Amina Ibrahim; Abed , Emad Moafaq; Utaiwi , Khawala Hadi (International Journal of Accounting and Economics Studies, 2025)
This research aims to specify the scientific procedures for applying lean accounting in Iraqi companies. The community of the re-‎research is made up of industrial companies in Diyala Governorate, and the Diyala General Electrical Industries Company, which was chosen ‎as a sample for this research. The most crucial results of this paper include: The traditional accounting system is appropriate to be use with ‎large-scale production. Therefore, if the economic unit desires to shift into using a lean production system, it must apply lean accounting. It ‎will create value for the customer, reduce loss, and manage the flow of the value. The application of lean accounting tools results in ‎the ability to reduce costs and quantity of inventory, increase quality, and the customer’s increased response in achieving their satisfaction. ‎Foremost among the key recommendations are: working on applying lean accounting tools due to the fact that they provide information for ‎making decisions and preparing reports clearly, as well as easily and in a timely manner‎.
Keywords: Accounting; Lean accounting; Industrial companies; Components